A novel pixel antenna by using a genetic algorithm for Wi-Fi 6E applications - Kayhan Çelik; Bekir Dursun; Javed Iqbal (Engineering Science and Technology, an International Journal)
The number of wireless devices is increasing daily, and these gadgets have become indispensable in people’s daily lives, requiring speedy and unlimited internet access. This may cause the currently used frequency bands to be insufficient or overcrowded. Adding the 6 GHz spectrum as a Wi-Fi 6E may assist in reducing traffic on other bands. However, the large bandwidth raises antenna design difficulties, and this article brings a new antenna proposal to this issue. It is a novel pixel patch antenna optimized by a metaheuristic optimization algorithm for Wi-Fi 6E applications. The shape of the radiating patch is determined using genetics, which is a basic algorithm based on population to achieve wideband operation. The antenna radiating element is divided into small pixel-shaped squares, then, some of them are removed for broadband operation. The antenna is constructed with the FR4 dielectric material, and it has a compact volume of 25 x 25 x 1.6 mm3. The measured impedance bandwidth of the antenna varies between 5.75 GHz and 8.46 GHz, with the maximum radiation efficiency and a gain of values of 67 % and 4.5 dBi. As a result, the suggested antenna may be employed for Wi-Fi 6E applications.